Pengaruh Umur, Status Perkawinan, Pendidikan, Pekerjaan, Dan Pengetahuan Terhadap Sikap Wanita Dalam Menghadapi Menopause (Studi di Kelurahan Pacar Kembang, Kecamatan Tambaksari, Kota Surabaya Tahun 2003) - Sila Pertikasari, Atik Choirul Hidajah (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Menopause is a natural process, which has to be through in woman s cycles of life. Menopause is often seen as an unpleasant period, because of the changes influenced the woman s physics and psychic and disturbing their activities. The objective of this research was to find out influence of characteristic such as: age, marital status, education, occupation, and knowledge of menopause to woman s attitude when they were dealing with menopause. Methods: This research were designed analytical and cross sectional. It was done in Pacar Kembang Village Tambaksari Subdistrict Surabaya: samples were 96 people choose by one stages cluster random sampling technique and multiple logistic regression test. Results: From the multiple logistic regression test with independent variable, the one influenced to women s attitude when dealing with menopause was age, with p < a (p = 0,010). Meanwhile, variables uninfluenced to women s attitude when dealing with menopause were marital status (p = 0,654), education (p = 1,000), occupation (p = 0,994) and knowledge of menopause (p = 1,000). Recommendation: Based on result of this research can be conclude that age have influenced to women s attitude when dealing with menopause. Therefore it is necessary to give more information about menopause as early as possible in order to get more attention to women when dealing with menopause. Keywords: women s attitude, menopause